Fishing for answers? Impacts of marine ecosystem quality on coastal tourism demand - Otrachshenko, Vladimir (2017)
The authors acknowledge the European Union 7th Framework Programme for Research and Technological Development (FP7) project VECTORS (Vectors of changes in marine life, impact on economic sectors), grant agreement no: 266445, under which the present research has been developed. Vladimir Otrachshenko wishes to thank financial support from Fundação para a Ciência e a Tecnologia (FCT), Portugal (PEst-OE/EGE/UI0124/2013). All opinions expressed are those of the authors and have not been endorsed by the FP7 and the FCT.